Ameliorative Potential of Glycyrrhiza glabra Extracts on Memory Impairments in Stress Triggered Rats - Kamboj, Parul; Thakur, Ajit K. (Current Traditional Medicine, 2021)
Background: Glycyrrhiza glabra Linn. (Family: Fabaceae) is known to be a very useful medicinal plant in the Traditional Medicinal Systems since centuries. With ethnopharmacological values, it is a well-reported plant for its anti-inflammatory, antioxidant, anxiolytic, expectorant and antidepressant activities. Objective: Although the plant has been described to possess memory enhancing activity, the present study focused on examining the comparative effect of Glycyrrhiza glabra extracts viz. flavonoid rich (GGFE) and glycyrrhizin rich (GGGE) in stress-triggered rats and providing future research insights on this herbal drug, for which no scientific justification has been reported till now. Methods: Male Wister rats divided into 7 different groups (n= 6 per group) were given chronic foot-shock stress for 21 successive days with scheduled administration of the extracts (50 and 100 mg/kg) and standard drug (10 mg/kg) for 28 days. Elevated Plus Maze, Rectangular Maze, Morris Water Maze, and Locomotor activity were performed to test behavioral alteration and learning ability of stressed rats. Further, rats were sacrificed to assay acetylcholinesterase activity and antioxidant activity in brain samples for their mechanistic role in learning and memory. Results: Extracts of Glycyrrhiza glabra indicated a significant alteration in stress-induced learning and memory deficiency in behavioral parameters studied. These extracts also modulated significant changes in acetylcholinesterase and antioxidant enzyme activity to improve the learning and memory of stressed rats. Conclusion: Both the extracts of Glycyrrhiza glabra (GGFE and GGGE) were found to exert memory enhancing property in stress-triggered rats. Moreover, the comparative results confirmed that the high potential of GGGE in comparison to GGFE might be due to the rich glycyrrhizin content present in GGGE responsible for acetylcholinesterase and antioxidant enzyme modulatory activities. Therefore, GGGE could be used as a promising lead for further mechanistic and molecular studies for defining the role of glycyrrhizin in Glycyrrhiza glabra.
Keywords: memory impairment